Chromosome races and polypoid cytoforms in Distichlis spicata - Reid, Scott D., author; Hughes, Harrison G., advisor; Koski, Anthony, advisor (Colorado State University. Libraries, 2001)
Saltgrass (Distichlis spicata [L.] Greene) is a salt-tolerant C4 grass native to the Americas that is currently being evaluated for use as a turfgrass species. Saltgrass has a highly variable morphology in different regional occurrences, and this has led some botanists to consider it as two species or as comprising several botanical varieties over its wide distribution in the U.S. west of the Mississippi River and along coastal regions. Chromosome numbers of 160 saltgrass accessions, primarily from nine western states, were determined. A 38-chromosome saltgrass race with distributions separate from the previously known 40-chromosome type has been identified. Both races are fertile and hybridize readily. The distribution pattern and the cytological behavior of hybrids between the races suggest they are adaptively different. No aneuploidy in the 38-chromosome race has been found, and no deficient aneuploids have been found in the 40-chromosome race. Meiotic irregularities in the 40-chromosome race suggest a pathway for the evolution of the 38-chromosome race, dependant on hypothesized genetic changes that allow fitness in individuals lacking the pair of homologues defining the difference between the races. More research is needed to evaluate broad but varied morphological differences between the races. The consequences of intermating the two cytoraces in breeding efforts are unknown, but karyotypic instability may result in some cases. An octaploid saltgrass cytotype, previously considered rare, has been found to occur more commonly, distributed among both of the cytoraces. One accession, believed to be a 6x cytotype, represents a ploidy level previously undescribed in saltgrass. Screening to identify individuals of different ploidy levels among collections made for the turfgrass breeding program is advisable. Aneuploidy and multivalent associations in meiosis suggest the higher-order polyploid cytoforms may reproduce with less efficiency sexually, but this has not been adequately studied. Two ca. 74-chromosome accessions showed high estimated pollen viability. B chromosomes are reported for the first time in saltgrass, occurring in some individuals of all three cytotypes.
Keywords: Grasses; Plants -- Effect of salt on